Thinking critically what does it mean? - Kubok, Dariusz (De Gruyter, 2018)
Analyses of the dynamics of change present in Europe are not complete without taking into account the role and function of the critical approach as a founding element of European culture. An appreciation of critical thinking must go hand-in-hand with reflection on its essence, forms, and centuries-long tradition. The European philosophical tradition has thematized the problem of criticism since its appearance. This book contains articles on the history of philosophical criticism and ways that it has been understood in European thought. Individual chapters contain both historical-philosophical and problem-oriented analyses, indicating the relationships between philosophical criticism and rationalism, logic, scepticism, atheism, dialectic procedure, and philosophical counseling, among others. Philosophical reflection on critical thinking allows for an acknowledgment of its significance in the fields of epistemology, philosophy of politics, aesthetics, methodology, philosophy of language, and cultural theory. The book should interest not only humanities scholars, but also scholars in other fields, as the development of an anti-dogmatic critical approach is a lasting and indispensible challenge for all disciplines.